2018
DOI: 10.1007/s11214-018-0469-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Global Unified Model of Europa’s Tenuous Atmosphere

Abstract: Despite the numerous modeling efforts of the past, our knowledge on the radiation-induced physical and chemical processes in Europa’s tenuous atmosphere and on the exchange of material between the moon’s surface and Jupiter’s magnetosphere remains limited. In lack of an adequate number of in situ observations, the existence of a wide variety of models based on different scenarios and considerations has resulted in a fragmentary understanding of the interactions of the magnetospheric ion population with both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 187 publications
5
61
0
Order By: Relevance
“…The asymmetry between leading and trailing hemisphere is controlled through the parameter A, where A = 0 results in a symmetric (Runs ".2") and A = 10 (adopted from Arnold et al, 2019) in an asymmetric density distribution (Runs ".3" and ".4"). In agreement with the model of Arnold et al (2019) and HST observations (Hall et al, 1995;Plainaki et al, 2018;Saur et al, 1998), we have chosen a neutral scale height of h 0 = 100 km and a surface density of n 0 = 5 · 10 13 m −3 .…”
Section: 1029/2019ja027346mentioning
confidence: 99%
“…The asymmetry between leading and trailing hemisphere is controlled through the parameter A, where A = 0 results in a symmetric (Runs ".2") and A = 10 (adopted from Arnold et al, 2019) in an asymmetric density distribution (Runs ".3" and ".4"). In agreement with the model of Arnold et al (2019) and HST observations (Hall et al, 1995;Plainaki et al, 2018;Saur et al, 1998), we have chosen a neutral scale height of h 0 = 100 km and a surface density of n 0 = 5 · 10 13 m −3 .…”
Section: 1029/2019ja027346mentioning
confidence: 99%
“…Another major contribution to these plasma currents arises from the interaction between the thermal magnetospheric flow and Europa's dilute atmosphere (e.g., Plainaki et al, ). The moon's gas envelope is partially ionized, mainly through electron impacts (Saur et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Paranicas et al () suggested that asymmetries in the flux of energetic electrons onto Europa's surface are the major cause of the H 2 SO 4 patterns seen in the moon's trailing hemisphere by Galileo. In addition, sputtering of Europa's surface by energetic ions was found to be the principal agent for the generation of the moon's dilute atmosphere (e.g., Plainaki et al, , ), consisting mainly of molecular oxygen (e.g., McGrath et al, ). Ultimately, the fraction of sputtered surface molecules that escapes Europa's gravity also forms the extended neutral gas torus along the moon's orbit; that is, Europa's surface serves as a source of particles for the Jovian magnetosphere (Johnson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These products react chemically to produce mostly O 2 and H 2 . Molecular oxygen is thought to be the most abundant species in the atmosphere, because it doesn't stick to the surface as much as other species (such as H 2 O) or escapes Europa's gravity easily (such as H 2 ) (Plainaki et al 2018). While sputtering is responsible for the extended, large scale height atmosphere, sublimation could also cause an additional low altitude confined atmospheric component with a much smaller scale height (Smyth and Marconi 2006).…”
Section: Europa As a Planetary Objectmentioning
confidence: 99%